Ibn Fūrak’s Methodology in Transforming the Ash’arite School into a Dialectical-Theological School - Ahmadi Ramchahi, Abdullatif; Abd Razzak, Monika @ Munirah; Najim Khalaf, Iman; Daryanavard., Soraya (Jurnal Usuluddin, 2016)
This study aims at studying the methodology of Ibn Fūrak in transforming the school of Abū al-Ḥasan al-Ashʿarī into a dialecticaltheological school through his book, ‘al-Mujarrad.’ To the best of the researchers’ knowledge, no theoretical study has examined Ibn Fūrak’s methodology particularly in what concerns the transformation of the Ash’arite School. This adopts the analytical inductive method to analyze the data. It begins by providing a brief introduction to Ibn Fūrak and Ash’arite School. This is followed by a discussion of his methodology in transforming the Ash’arite School into one that is dialectical-theological. This discussion is divided into three components modelled after Ibn Fūrak’s approach, namely establishing a scholarly method to compile alAshʿarī’s opinions and theological theories, applying al-Ashʿarī’s methodology and school of thought in his school in Nishabur, and educating his students on Ash’arite theology.